Assessment of health related quality of life of asthma patients in a tertiary care teaching hospital - Patil, Shrishailgouda S.; Oggu, Archana; Jayachandran, Shravan; Patil, Neha; Doddayya, H. (International Journal Of Community Medicine And Public Health, 2019)
Background: The present study is planned to assess the health related quality of life (HRQoL) in asthma patients by using HRQoL questionnaire (SF-36 v2). Methods: A prospective observational study was conducted for a period of 6 months (September 2017 to February 2018) in Navodaya Medical College Hospital and Research Centre, Raichur on a total of 108 patients of either sex suffering from persistent asthma. The HRQoL of asthma patients was measured by face-to-face interview using HRQoL questionnaire (SF-36v2). Results: Female patients were found to be more affected with asthma compared to male patients and the prevalence of asthma is found to be more in the middle aged and elderly patients compared to adults. The important triggering factors for the asthma were found to be exposure to dust, smoking, alcohol and cooking fuel. The mean physical component summary (PCS) scores is 47.46 (±15.56) and the mean mental component summary (MCS) scores is 66.73 (±13.59). The findings of our study reveals that the physical HRQoL is more affected compared to mental HRQoL as revealed by PCS and MCS scores. Conclusions: The findings of our study conclusively suggest that the physical HRQoL is more affected than mental HRQoL in asthma patients and also the need to improve the quality of life in these patients by appropriate patient education regarding the triggering factors of asthma, preventive measures and the medication adherence.